Analisis Tegangan dan Arus DC pada Busbar Menuju Plat Anoda dan Katoda dalam Proses Elektrolisis di Unit Chemical Plant PT. Toba Pulp Lestari, Tbk - Napitupulu, Natanael; Karti, Karti (CV. IRA PUBLISHING, 2024)
This electrolysis cell is used to convert sodium hydroxide into sodium chloride. This study aims to measure the voltage and DC passing through the cathode and anode plates during the electrolysis process. The power source used in this process provides a DC voltage of 70 volts, a DC of 8 A, and a resistance of 8.75 Ω. The sodium hydroxide solution can be transformed into sodium chloride at PT with this current and voltage. Toba Pulp Lestari Tbk, Porsea, is in the chemical plant unit, and this electrolysis cell operates optimally. It produces a significant amount of sodium chloride, used as a compound in making paper pulp. The analysis results indicate that the types of anode and cathode plates effectively conduct electricity in the electrolysis cell, aided by busbars as conductors.